Taxonomic changes in C4 Cyperus (Cypereae, Cyperoideae, Cyperaceae): combining the sedge genera Ascolepis, Kyllinga and Pycreus into Cyperus s.l. - Larridon, Isabel; Bauters, Kenneth; Reynders, Marc; Huygh, Wim; Goetghebeur, Paul (Phytotaxa, 2014)
The sedge genera Alinula, Ascolepis, Kyllinga, Lipocarpha, Pycreus, Queenslandiella, Remirea, Sphaerocyperus and Volkiella (Cyperaceae) were recognised at generic level because they possess specialised inflorescence and/or flower characters. However, recent molecular phylogenetic analyses show that these genera are all nested in a paraphyletic Cyperus s.s. and therefore should be viewed as part of a broadly circumscribed genus Cyperus. For all species of Alinula and for the single species of Queenslandiella, Remirea and Sphaerocyperus, Cyperus names were already published by other authors. For the species of Lipocarpha and Volkiella, Cyperus names and a new sectional classification are published in a separate paper including a detailed molecular phylogenetic hypothesis for these taxa. Based on a study of herbarium specimens and literature, in this paper, twenty species of Ascolepis, seventeen species of Kyllinga, and six species of Pycreus, which do not yet have a validly published and legitimate name in Cyperus, are formally included into Cyperus as new combinations or new names. Notes on the synonymy of an African Pycreus species are also included.